Survival and complications in cats treated with subcutaneous ureteral bypass. (14th September 2020) - Kulendra, N. J.; Borgeat, K.; Syme, H.; Dirrig, H.; Halfacree, Z.
Abstract : Objectives: To report the complications and factors affecting outcome for cats following placement of a subcutaneous ureteral bypass (SUB™). Materials and Methods: In this retrospective study, complications, the presence of a urinary tract infection and survival time were recorded following subctutaneous ureteral bypass placement. Factors affecting survival time were assessed using a Kaplan Meier curve and log rank test. Results: Ninety‐five cats had 130 subcutaneous ureteral bypasses placed. Ten cats did not survive to discharge. Forty cats died or were euthanised after discharge (42%); the median survival time of these cats was 530 days (range 7 to 1915). Minor complications occurred in 18 cats (19%) and major complications occurred in 46 cats (48%), the majority of which were after hospital discharge. Twenty‐seven cats were diagnosed with a urinary tract infection (UTI) post‐operatively. A significant association between long‐term survival and creatinine at presentation was identified. The median survival time for cats presenting with creatinine concentration ≥440 μmol/L (International Renal Interest Society stage acute kidney injury (AKI) 4 and 5) was 530 days (95% CI 273–787 days), compared to a median survival time of 949 days (95% CI 655–1243 days; Log Rank P=0.024) for those cats presenting with creatinine <440 μmol/L (International Renal Interest Society stage AKI 1–3). Clinical Significance: In this population of cats, subcutaneous ureteral bypass placement was associated with an approximately 10% in‐hospital mortality and a high complication rate. Most complications were manageable, resulting in an overall median survival time of over 2 years.